Status of heavy metals in tissues of wedge clam, Donax faba (Bivalvia: Donacidae) collected from the Panambur beach near industrial areas - Singh, Yambem Tenjing; Krishnamoorthy, Machina; Thippeswamy, Seetharamaiah (Recent Research in Science and Technology, 2012)
The wedge clam, Donax faba are edible bivalves and consumed as seafood. We found out the concentrations of Cu, Pb, Fe, Cr and Ni in the tissues of the wedge clams in coastal site, Panambur located along the south west coast of Karnataka. The concentrations of heavy metals in the samples were determined by atomic absorption spectrophotometer (AAS, GBC 932plus) working with an air acetylene flame. D. faba showed seasonal variations of metals accumulation with maximum concentrations during all seasons occurred in our study. The analysis of Fe content showed higher average concentrations for wedge clam collected from the study site. The concentration was in the order of Fe>Cu>Cr>Ni>Pb in our present study. The levels of heavy metals like Cu, Pb and Cr in the whole tissue of D. faba were below permissible limits except Ni. High concentrations of metals in the whole tissue of wedge clams collected may be derived from the industrial areas and a variety of anthropogenic activities.